1992
DOI: 10.1038/355359a0
|View full text |Cite
|
Sign up to set email alerts
|

9-Cis retinoic acid stereoisomer binds and activates the nuclear receptor RXRα

Abstract: Vitamin A (retinol) and its natural derivatives are required for many physiological processes. The activity of retinoids is thought to be mediated by interactions with two subfamilies of nuclear retinoic acid receptors, RAR and RXR. The RARs bind all-trans retinoic acid (t-RA) with high affinity and alter gene expression as a consequence of this direct ligand interaction. RXR alpha is activated by t-RA, yet has little binding affinity for this ligand. t-RA may be converted to a more proximate ligand that direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
540
0
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,184 publications
(566 citation statements)
references
References 33 publications
12
540
0
9
Order By: Relevance
“…RARs bind and are activated by all-trans RA and its 9-cis isomer (Zelent et al, 1989;Allenby et al, 1993), while RXRs bind and are activated by 9-cis RA only Levin et al, 1992;Mangelsdorf et al, 1992). Transcriptional activation through retinoic acid response elements is thought to be mediated by heterodimer formation between RAR and RXR family members, or by homodimer formation of RXRs (Leid et al, 1992a;Zhang et al, 1992;Heery et al, 1993;GigueÁ re, 1994;Glass, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…RARs bind and are activated by all-trans RA and its 9-cis isomer (Zelent et al, 1989;Allenby et al, 1993), while RXRs bind and are activated by 9-cis RA only Levin et al, 1992;Mangelsdorf et al, 1992). Transcriptional activation through retinoic acid response elements is thought to be mediated by heterodimer formation between RAR and RXR family members, or by homodimer formation of RXRs (Leid et al, 1992a;Zhang et al, 1992;Heery et al, 1993;GigueÁ re, 1994;Glass, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The natural ligand for RARs is all-trans-retinoic acid (ATRA), whereas the stereoisomer 9cRA binds to both RARs and RXRs with high affinity (Giguere et al, 1987;Petkovich et al, 1987;Heyman et al, 1992;Levin et al, 1992). RXRs also play a very important role in heterodimerization with other nuclear receptors such as VDR and RARs.…”
mentioning
confidence: 99%
“…[14][15][16][17] Whereas all-trans RA binds only RARs, 9-cis RA binds and activates both RARs and RXRs. [18][19][20] Preclinical studies also showed that 9-cis RA was more potent than all-trans RA in inducing myeloid differentiation in HL60 cells. 21,22 In a preliminary report, we found that 9-cis RA could induce complete remission in APL, but the drug did not appear capable of reversing clinically acquired retinoid resistance.…”
Section: Introductionmentioning
confidence: 99%